The Semantic Extension of Body Parts in Afan Oromo Idiomatic Expression - Bekele Feyisa, Alem (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2021)
This study was conducted with the intent of describing the semantic extension of body parts in Afan Oromo idiomatic expression. The parts of the body that were highly used by the society, the purposes and the effects of using the expression, and also parts of the communities that are affected in the use of the expressions have been assessed. A qualitative approach, with a descriptive survey research design, was employed. To collect data, interviews with guided questions were used. Accordingly, among the total number of 33 participants, 21 Afan Oromo instructors from Madda Walabu, Bule Hora, and Arsi Universities were selected by the snowball sampling method. In addition, 3 administrators and 9 experts from the Culture and Tourism Offices of Arsi, Bale, and Guji Zone were selected by purposive sampling technique. Besides, relevant data of this study was obtained from and is collected through document review. The findings show that the parts of the body that the society is highly used, the functions and effects of the communication expression, parts of the communities that are affected when the expression is used. Finally, the study came up with the role of these expressions in language use. Therefore, studying idioms and motivating the researchers for further work on these areas to help the language to develop, and to use it in a very natural and attractive way. It is also used to reduce the problem of misunderstanding in utterances and language learning.